Cardiovascular safety and hemodynamic considerations in oncology drug development – webinar highlights October 10th 2012. (September 2013) - Braddock, Martin; Heilbraun, Jeff; Mendzelevski, Boaz
Abstract : Introduction: Development of new drugs in oncology may have implications for cardiovascular risk. This report describes some aspects of our growing knowledge in the area of evaluating benefit–risk and may be of direct importance to scientists working in drug discovery and development. Areas covered: This report of webinar highlights entitled "Trends in CardiOncology: the evolution of blood pressure and electrocardiogram (ECG) Markers" covers the current state of pharmacology of selected drugs which induce blood pressure elevation and best practices in employing the measurement of blood pressure elevation and cardiac safety parameters for drug development in oncology. Expert opinion: Oncology drug-induced cardiotoxicity has recently been recognised as an important drug development and clinical issue. The recognition of the risks and opportunities has prompted intensive research into mechanisms of chemotherapy-induced cardiotoxicity and potential prevention strategies. Drug-induced blood pressure elevation has emerged as a key area of interest, both as a marker of efficacy of vascular targeted chemotherapies as well as a target for early intervention strategies. While further research is ongoing, current data strongly suggest that early intervention strategies may provide significant short- and long-term clinical benefits to cancer patients undergoing chemotherapy.